Multidimensional Muslim Family Resilience During the COVID-19 Pandemic: A Case Study on Divorce Rate - Muslih, Moh; Umi Mahmudah; Anik Maghfiroh; Muhammad Sulaiman Salim (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
The pandemic of COVID-19 had a profound impact on the lives of families worldwide, including Muslim families in Indonesia. This study analyzes the resilience of multidimensional Muslim families in Indonesia during the COVID-19 pandemic. It has also been linked to family resilience in preventing divorce, which has reportedly increased during the COVID-19 pandemic. This study uses a qualitative approach. Observation techniques and in-depth interviews are conducted to obtain primary data. There are 25 interviewees. The findings indicate that three dimensions, namely the individual, family, and community dimensions, influence the resilience of multidimensional Muslim families during the COVID-19 pandemic. There is a positive causality relationship between the three interconnected dimensions. The findings suggest that all three can be used to prevent divorce by increasing resilience in these three dimensions. The analysis also reveals a spike in domestic violence, which is the cause of divorce during the COVID-19 pandemic. Domestic violence affects not only wives but also husbands.